ANALISIS ARUS KAS UNTUK MENILAI KINERJA KEUANGAN PERUSAHAAN (Studi Kasus Pada PT POS Indonesia (Persero) Tahun 2014- 2018) - Ria Avriyanti; Dewi Saptantinah; Djoko Kristianto (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2020)
ThisSstudyaaims tozanalyze the cash flow statement inaassessingtheccompany's financialpperformance. The benchmarks useddin assessingfinancial performance are operatingccash flowwratio, cash-toointerest coverageratio, capitaleexpenditureeratio, total debt ratio, cash-to-current debt coverageratio, cash flow adequacy ratio, fund flow coverage ratio, and net cash flow ratio.free. This study uses a descriptive qualitative method, with the sample used is thePT POS Indonesia (Persero) cash flow statement from 2014 to 2018. Theresultssof theaanalysis of thissstudysshowwthat the financial performance of thePT POS Indonesia (Persero) company is not good. Because of the eight ratiocalculations, only three ratios meet the standard ratio of one. The results of theTrend in financial performance show that the four ratios consisting of operatingcash flow ratios, total debt ratios, cash coverage ratios to current debts, and fundflow coverage ratios have an increasing Trend while the cash to interestcoverage ratio, capital expenditure ratios, adequacy ratios cash flow, and theratio of net free cash flow has a downward Trend.